Promethee II and the Multiple Criteria Performance Analysis: The Comparison of Telecommunications Sectors in North Africa - Karim SABRI (Communications of International Proceedings, 2021)
In North African countries (Algeria, Morocco, Mauritania and Tunisia), a considerable improvement of the situation of the telecommunication operators has been noticed during the nineties. The evolution in these countries was very different depending on their economic policies, their effort of reorganization of their telecommunication sector and their technological change. These differences will be exhibited and analysed by comparing the operators’ performances over a decade (1992–2001). Our approach is based on the Promethee II method and the software ARGOS, a multiple criteria analysis is performed, taking into account a larger scope of analysis. This method of analysis provide the two dimensions of performance for Promethee: that are the service to the community and the enterprises performances, often in conflict.
Keywords: Case study; multiple criteria decision aid; Promethee; African telecommunications re-forms; dynamic performance analysis.